Validation of an insertion-engineered isoprene synthase as a strategy to functionalize terpene synthases. Issue 48 (8th September 2021) - Gonzalez-Esquer, C. Raul; Ferlez, Bryan; Weraduwage, Sarathi M.; Kirst, Henning; Lantz, Alexandra T.; Turmo, Aiko; Sharkey, Thomas D.; Kerfeld, Cheryl A.
Abstract : "Insertion-engineering" approach allows for the modification of αβ terpene synthases. Abstract : Terpene synthases are biotechnologically-relevant enzymes with a variety of applications. However, they are typically poor catalysts and have been difficult to engineer. Structurally, most terpene synthases share two conserved domains (α- and β-domains). Some also contain a third domain containing a second active site (γ-domain). Based on the three-domain architecture, we hypothesized that αβ terpene synthases could be engineered by insertion of a heterologous domain at the site of the γ-domain (an approach we term "Insertion-engineering terpene synthase"; Ie-TS). We demonstrate that by mimicking the domain architecture of αβγ terpene synthases, we can redesign isoprene synthase (ISPS), an αβ terpene synthase, while preserving enzymatic activity. Insertion of GFP or a SpyCatcher domain within ISPS introduced new functionality while maintaining or increasing catalytic turnover. This insertion-engineering approach establishes that the γ-domain position is accessible for incorporation of additional sequence features and enables the rational engineering of terpene synthases for biotechnology.